New perspectives in relationship marketing conceptualization - GÂRDAN, Daniel Adrian (Annals of Spiru Haret University. Economic Series, 2011)
Relationship marketing represents a concept that has been disputed in the last 15 years as being a true paradigm of marketing thinking, or just a new method to apply marketing techniques to the new requirements and transformations into the socio-economic field of contemporary economy. Developing the conceptualization of relationship marketing has involved a wide area of research both in the theoretical and practical background. But despite many controversies about how to apply relationship marketing, at a profound level, the openness to new modalities for managing relationships with consumers, in the context of developing a new type of consumer – the postmodern consumer – is one of the undeniable strengths of relationship marketing. The present article is trying to capture some of the possible directions of development of relationship marketing techniques considered by the author as being a kind of future trends of this complex scientific approach. In a brief we consider as appropriate for companies in the consumer markets to develop relationship marketing strategies around the concept of “consumer personal brands basket”. Considering this, every company should try to put together strategic resources and develop common activities with other producers from the brands basket for a certain consumer. Due to the technological development and diminishing costs for management of large and complex consumer databases, developing such a strategic orientation could be not only an illusion but a simple solution for consumers and tomorrow’s competitive environment.